(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
Silond catfish Silonia silondia is one of the food fishes high in nutritional value in Asian countries. However, natural populations have seriously declined or are on the verge of extinction due to over-exploitation and various ecological changes in its natural habitats, leading to an alarming situation which deserves high conservation attention. This paper suggests conservation measures that should be considered towards the preservation of the remnant isolated population of this fish in Asian countries. Res. Agric., Livest. Fish.5(2): 235-240, August 2018